New hydrogen-bonding organocatalysts: Chiral cyclophosphazanes and phosphorus amides as catalysts for asymmetric Michael additions - Klare, Helge; Neudörfl, Jörg M.; Goldfuss, Bernd (Beilstein Journal of Organic Chemistry, 2014)
Ten novel hydrogen-bonding catalysts based on open-chain PV-amides of BINOL and chinchona alkaloids as well as three catalysts based on rigid cis-PV-cyclodiphosphazane amides of N1,N1-dimethylcyclohexane-1,2-diamine have been developed. Employed in the asymmetric Michael addition of 2-hydroxynaphthoquinone to β-nitrostyrene, the open-chain 9-epi-aminochinchona-based phosphorus amides show a high catalytic activity with almost quantitative yields of up to 98% and enantiomeric excesses of up to 51%. The cyclodiphosphazane catalysts show the same high activity and give improved enantiomeric excesses of up to 75%, thus representing the first successful application of a cyclodiphosphazane in enantioselective organocatalysis. DFT computations reveal high hydrogen-bonding strengths of cyclodiphosphazane PV-amides compared to urea-based catalysts. Experimental results and computations on the enantiodetermining step with cis-cyclodiphosphazane 14a suggest a strong bidentate H-bond activation of the nitrostyrene substrate by the catalyst.
Keywords: DFT computations; hydrogen bonding; Michael addition; organocatalysis; phosphazanes